2012
DOI: 10.1163/156853812x624423
|View full text |Cite
|
Sign up to set email alerts
|

Mating system and population analysis of the broad-snouted caiman (Caiman latirostris) using microsatellite markers

Abstract: The knowledge about reproductive strategies of a species contributes to their conservation. Multiple paternity is a reproductive behavior increasing effective population size, which could increase genetic diversity particularly in populations submitted to bottlenecks events. In Argentina, wild populations of Caiman latirostris are subject of a management plan devoted to their preservation and sustainable utilization based on its commercial interest. This program started in response to the evident numeric reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 58 publications
(70 reference statements)
0
18
0
Order By: Relevance
“…From Table 1, when the total number of alleles for each crocodilian parentage analysis study are tallied, the number of alleles varies from 24 (Amavet et al, 2012;Hu & Wu, 2010) to 91 alleles (Oliveira et al, 2014) with an average of 42 total alleles equivalent to the 5H panel used herein. Following from the findings in this study and given that nest assignment is possible in crocodilians if offspring are being sampled from eggs/embryos, when fewer alleles are available, using GERUD 2.0 or the SLMM is sufficient to accurately infer sire number.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From Table 1, when the total number of alleles for each crocodilian parentage analysis study are tallied, the number of alleles varies from 24 (Amavet et al, 2012;Hu & Wu, 2010) to 91 alleles (Oliveira et al, 2014) with an average of 42 total alleles equivalent to the 5H panel used herein. Following from the findings in this study and given that nest assignment is possible in crocodilians if offspring are being sampled from eggs/embryos, when fewer alleles are available, using GERUD 2.0 or the SLMM is sufficient to accurately infer sire number.…”
Section: Discussionmentioning
confidence: 99%
“…Of the studies conducted since then, up to ten males have been inferred to sire captive saltwater crocodile (Crocodylus porosus ) nests (Lewis, FitzSimmons, Jamerlan, Buchan, & Grigg, 2013) although 1 -3 sires are most commonly reported (Table 1). Further, between 17% (Amavet, Vilardi, Rueda, Larriera & Saidman, 2012) and 100% (Milián-García et al, 2016) of nests have been shown to be multiply sired. Some studies have used a small subset of nests from only one nesting season (eg n = 4 nests from Amavet, Rosso, Markariani & Piña, 2008) whilst others have conducted longitudinal studies over multiple years (Lance et al, 2009) including up to 151 nests over six consecutive years (Zajdel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In A. mississippiensis , the vagina is surrounded by thick layers of smooth muscle (Gist, Bagwill, Lance, Sever, & Elsey, 2008); similar anatomy in C. latirostris would allow females to prevent fecal matter from entering the reproductive tract and also provide a method by which they can control whether cloacally placed semen or the male glans tip enters the vagina during copulation. There is evidence that female crocodylians are polygamous (Amavet, Vilardi, Rueda, Larriera, & Saidman, 2012; Davis, Glenn, Elsey, Dessauer, & Sawyer, 2001; Lewis, FitzSimmons, Jamerlan, Buchan, & Grigg, 2013; McVay et al, 2008; Oliveira, Marioni, Farias, & Hrbek, 2014) and can store sperm (Davenport, 1995; Gist et al, 2008). In the American alligator, stored sperm is found in oviductal glands rostral to the vagina (Gist et al, 2008); C. latirostris has similar oviduct anatomy (Galoppo et al, 2016) and is likely to store sperm in a similar fashion.…”
Section: Discussionmentioning
confidence: 99%
“…No. 3, 4, and 5 in Monteiro et al, 2002) The degree of relationship (r) among siblings was taken as r5 0.50 for all nests, as it was assumed that individuals were full siblings (see Amavet et al, 2009Amavet et al, , 2012. Heritability for each univariate character was calculated as h 2 5 t/r (Falconer and Mackay, 1996).…”
Section: Methodsmentioning
confidence: 99%